1994
DOI: 10.1042/bj3020709
|View full text |Cite
|
Sign up to set email alerts
|

Inositol trisphosphate metabolism in Saccharomyces cerevisiae: identification, purification and properties of inositol 1,4,5-trisphosphate 6-kinase

Abstract: Ins(1,4,5)P3 metabolism was examined in Saccharomyces cerevisiae extracts. S. cerevisiae contains readily detectable Ins(1,4,5)P3 kinase activity that is predominantly soluble, but phosphomonoesterase activity acting on Ins(1,4,5)P3 was not detected in either soluble or particulate preparations from this organism. We have purified the kinase activity approximately 685-fold in a rapid four-step process, and obtained a stable preparation. The enzyme has an apparent native molecular mass of approximately 40 kDa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 44 publications
4
35
0
Order By: Relevance
“…Originally, one of us suggested that the appearance of Ins(1,4,5)P 3 3-kinase was also early and preceded the split between plants and animals [26]. However, the Chlamydomonas Ins(1,4,5)P 3 kinase [25], whose existence led to this suggestion, can now be seen probably to be akin to the Ins-(1,4,5)P 3 3/6-kinases discussed above [6,22,23] in so far as it has a low a¤nity for Ins(1,4,5)P 3 , no detectable regulation by Ca 2 and (assuming it is only one enzyme) it converts its InsP 4 product(s) directly into Ins(1,3,4,5,6)P 5 . Thus, the`classic' Ca 2 -regulated Ins(1,4,5)P 3 3-kinases [1,3] may now be viewed as not so much a central part of inositol phosphate metabolism, but rather as separate, and late, addition to the repertoire of Ins(1,4,5)P 3 metabolism following the evolution of this molecule as a second messenger.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Originally, one of us suggested that the appearance of Ins(1,4,5)P 3 3-kinase was also early and preceded the split between plants and animals [26]. However, the Chlamydomonas Ins(1,4,5)P 3 kinase [25], whose existence led to this suggestion, can now be seen probably to be akin to the Ins-(1,4,5)P 3 3/6-kinases discussed above [6,22,23] in so far as it has a low a¤nity for Ins(1,4,5)P 3 , no detectable regulation by Ca 2 and (assuming it is only one enzyme) it converts its InsP 4 product(s) directly into Ins(1,3,4,5,6)P 5 . Thus, the`classic' Ca 2 -regulated Ins(1,4,5)P 3 3-kinases [1,3] may now be viewed as not so much a central part of inositol phosphate metabolism, but rather as separate, and late, addition to the repertoire of Ins(1,4,5)P 3 metabolism following the evolution of this molecule as a second messenger.…”
Section: Resultsmentioning
confidence: 98%
“…been reported from yeast [6,22,23], higher plants [24] and probably also Chlamydomonas [25], though none of them has yet been cloned. We could detect no activity against [ 32 P]Ins(1,3,4,5)P 4 (not shown) and we should note also that PiUS shows no obvious sequence similarity with the mammalian or Arabidopsis Ins(1,3,4)P 3 5/6-kinases [4,5] nor with the recently identi¢ed Ins(1,3,4,5,6)P 5 2-kinase from yeast [6].…”
Section: Resultsmentioning
confidence: 99%
“…The phosphatidylinositol 3Ј-kinase inhibitor wortmannin was used at 100 nM as a control for inhibition of cellular PKB activity. (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…Yeast cells contain many of the components known to be involved in mammalian phosphoinositide metabolism, including PIP 2 , IP 3 , DAG, phospholipase C, protein kinase C (PKC), calmodulin and Ca/calmodulin-dependent protein kinase (Thevelein, 1994). As in mammalian cells, breakdown of PIP 2 and an increase in IP 3 and DAG occur in response to at least one extracellular signal: nitrogen (Schomerus and Kuntzel, 1992 gene (which encodes PKC) are essential for yeast cell proliferation (Uno et al, 1988;Levin and BartlettHeubusch, 1992;Flick and Thorner, 1993;Payne and Fitzgerald-Hayes, 1993;Yoko-o et al, 1993;Estevez et al, 1994). If PIP 2 is involved in signalling, then there should be intracellular stores of Ca 2þ that are sensitive to IP 3 .…”
Section: Introductionmentioning
confidence: 99%